USAHA KECIL DAN PEREMPUAN SEBAGAI PELAKU USAHA - Widoyono Widoyono (Benefit: Jurnal Manajemen dan Bisnis, 2004)
In fact, the difference of sex causes impact for dividing role between woman and man that it causesmany losses for woman’s position whether as a formal public worker or an agent of small business.Although it is not maximal yet, gender mainstreaming causes changing of woman’s life in nationaldevelopment (economic). Woman as an agent of small business has some opportunities and challenges.Woman’s opportunity term of policy which priorities pengarusutamaan gender for agent of businesseffects funding and improving skill that its business can increase and survive, behind of entrepreneurshipspirit and flexibility. Woman’s challenge as an agent of business is sourced on structure and culture ofthe society, which is still characterized by patriarchy. Society should realize that woman is human whois same as man that it needs acknowledgment for woman who is as an agent of small business, becausethe microeconomic activity done by woman has a significant influence on development of macroeconomic.